Analysis System Security Door Using The Finger Print Based On Micro Controller - Sugandasari E; Aprilinda Y (Bandar Lampung University (UBL), 2017)
Along with the development of science and technology, Security system is now very needed, One of the security system on the door. the security of the door is very important for the room in question. The purpose of this research is to analyze the door security system using finger print sensor. Fingerprint system is by recognizing the pattern offingerprint. By using this fingerprint pattern has a high level of security, it is proven this system has been widely used in offices, companies, schools, government, hospitals etc. In addition to having a high level of security, fingerprint pattern system is also easier to use. This fingerprint sensor checks whether there is a match between the data obtained from the verification process and the data stored in the database, what data when it matches the door will open. The process of automation on the door is controlled using a microcontroller so it can move the relay and set the automation on the door in accordance with the data obtained.